Otorhinolaryngology, Head and Neck Surgery - Anniko, Matti; Bernal-Sprekelsen, Manuel; Bonkowsky, Viktor; Bradley, Patrick J.; Iurato, Salvatore; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The aim of this book is to harmonize the field of Otorhinolaryngology, Head and Neck Surgery and its interdisciplinary subjects within the European Community; to present the state-of-the-art in the field and to give standards for diagnostic and therapeutic procedures. The book includes sections titled Head and Neck, Larynx and Trachea, Nose and Paranasal Sinuses, Oral Cavity and Oropharynx, and Otology and Neurotology. It also covers such topics as patient evaluation and treatment, basic surgical procedures, as well as more conservative approaches. The book is authored by renowned experts throughout Europe, and features a layout that facilitates quick and easy retrieval of information.
Otology and Neurotology -- Basics -- Malformations of the Ear -- Diseases of the Auricle and of the External Auditory Canal -- Middle Ear -- Middle Ear/Inner Ear -- Inner Ear -- Facial Nerve -- Diseases of the Nose and Paranasal Sinuses -- Anatomy of the Nasal Cavity and Paranasal Sinuses -- Physiology of the Nose -- Examination of the Nasal Cavity and Paranasal Sinuses -- Functional Investigations of the Nose -- Imaging of the Nasal Cavity and Paranasal Sinuses: Anatomy and Anatomic Variations -- Diseases of the Outer and Inner Nose -- Epistaxis -- Congenital Malformation: Choanal Atresia -- Nasal Obstruction -- Nonallergic Rhinitis and Primary Ciliary Dyskinesia -- Allergic Rhinitis -- Acute Sinusitis -- Chronic Rhinosinusitis: Definition, Diagnostics and Physiopathology -- Nasal Polyposis -- Specific Sinusitis -- Complications of Sinusitis -- Principles of Functional Endoscopic Sinus Surgery -- Endoscopic Dacryocystorhinostomy: from Diagnosis to Surgery -- Trauma of the Paranasal Sinuses and Orbit -- Endoscopic Repair of Anterior Skull Base Defects -- Smell Disorders -- Benign Sinonasal Neoplasms -- Malignant Tumours of the Paranasal Sinuses and the Anterior Skull Base -- Headache and Facial Ache -- Diseases of the Nasopharynx -- Basics -- Adenoiditis -- Adenoids -- Tumours of the Nasopharynx -- Diseases of the Salivary Glands -- Salivary Gland Anatomy -- Saliva, Salivation and Functional Testing -- Clinical Examination and Limited Investigations of Salivary Gland Diseases -- Trauma to the Salivary Glands and their Management -- Inflammatory and Non-Inflammatory Affections of the Salivary Glands -- Sjögrens Syndrome and Sialosis -- Salivary Glands: Benign Tumours -- Primary and Secondary Malignant Salivary Gland Neoplasms -- Salivary Gland Surgery: Principles -- Diseases of the Oral Cavity, Oropharynx, Hypopharynx, Cervical Esophagus -- Oral Cavity -- Oropharynx and Hypopharynx -- Oesophagus -- Nasopharynx -- Diseases of the Larynx -- Anatomy and Physiology of the Larynx and Hypopharynx -- Office Examination -- Inflammatory Diseases and Lasers -- Mucosal Disease of the Glottis -- Benign Neoplasms and Other Tumours of the Larynx -- Laryngeal Cancer -- Trauma to the Laryngeal and Tracheal -- Laryngeal and Tracheal Stenosis in Children and Adults -- Laryngeal Nerve Disorders -- Basic Surgical Procedures on the Respiratory Tract: Laryngoscopy, Tracheoscopy and Including Tracheostomy -- Laryngeal, Hypopharyngeal and Tracheal Imaging -- Voice Disorders -- Voice Disorders: Classification -- Voice Evaluation and Respiratory Function Assessment -- Phonosurgery -- Diseases of the Thyroid Gland: Diagnostics and Treatment -- Hashimoto s Thyroiditis -- Graves s Disease -- Other Causes of Thyrotoxicosis -- Multinodular Goitre -- Thyroid Regulation and Dysfunction in the Pregnant Patient -- Thyroid Carcinoma -- Surgical Options for Thyroid Malignancy -- Surgery of the Thyroid Gland -- Head and Neck Tumors -- Cysts and Benign Tumours of the Neck -- Malignant Tumours of the Neck -- Malignant Lymphomas in the Ear, Nose and Throat Area -- Clinical Examination and Diagnostic Techniques in Head and Neck Oncology -- Interpretation of Relevant Imaging -- Head and Neck Tumours -- Principles and Techniques of Neck Dissection -- Carcinoma of Unknown Primary Syndrome -- Ear, Nose and Throat Anaesthesia -- Ear, Nose and Throat Anaesthesia.
Keywords: Medicine; Otorhinolaryngology; Surgery; Medicine & Public Health; Otorhinolaryngology; Plastic Surgery